A Giant Bulk‐Type Dresselhaus Splitting with 3D Chiral Spin Texture in IrBiSe. Issue 4 (12th February 2020) - Liu, Zhonghao; Thirupathaiah, Setti; Yaresko, Alexander N.; Kushwaha, Satya; Gibson, Quinn; Xia, Wei; Guo, Yanfeng; Shen, Dawei; Cava, Robert J.; Borisenko, Sergey V.
Abstract : Materials with giant spin splitting are desired for spintronic applications. The fabrications of spintronic devices from half metals with one spin direction are often hampered, however, by stray magnetic fields, domain walls, short spin coherence times, scattering on magnetic atoms or magnetically active interfaces, and other characteristics that come along with the magnetism. The surfaces of topological insulators, or Dirac/Weyl semimetals, could be an alternative, but production of high‐quality thin films without the presence of the bulk states at the Fermi energy remains very challenging. Here, by utilizing angle‐resolved photoemission spectroscopy, a record‐high Dresselhaus spin–orbit splitting of the bulk state in the nonmagnetic IrBiSe is found. The band structure calculations indicate that the splitting band is fully spin‐polarized with 3D chiral spin texture. As a source of spin‐polarized electrons, lightly doped IrBiSe is expected to generate electric‐field‐controlled spin‐polarized currents, free from back scattering, and could host triplet and Fulde–Ferrel–Larkin–Ovchinnikov (FFLO) superconductivity. Abstract : By utilizing angle‐resolved photoemission spectroscopy, a record‐high Dresselhaus spin–orbit splitting of the bulk state in the nonmagnetic IrBiSe is found. The band structure calculations indicate that the splitting band is fully spin‐polarized with 3D chiral spin texture. As a "nonmagnetic half‐metal, " lightly doped IrBiSe is expected to generate electric‐field‐controlled spin‐polarized currents free from back scattering.